Physical activity during pregnancy and childhood obesity : systematic review and meta-analysis - Barakat Carballo, Rubén (2024)
The repercussions of childhood overweight and obesity are multifaceted, extending beyond the realm of physiology and giving rise to psychological and emotional disturbances in affected children. The precise effects of gestational physical activity (PA) on parameters related to childhood overweight and obesity remain inadequately understood. The aim of this study (Registration CRD42022372490) was to evaluate the literature regarding the influence of PA during pregnancy on the risk of childhood overweight and obesity. Materials and Methods: Only randomized controlled trials (RCTs) were considered for inclusion. Determinant parameters of childhood obesity were analyzed. A total of 30 studies involving 16,137 pregnant women were examined. Five meta-analyses about the effects of PA during pregnancy on determinants of childhood overweight and obesity were conducted. Results: Although favorable trends were observed, Meta-Analyses showed no statistical differences in the effects of PA on weight at birth (Z = 0.03, p = 0.97), Ponderal Index at birth (Z = 0.64, p = 0.52), Macrosomia and Large for Gestational Age at birth (Z = 0.93, p = 0.35), children’s BMI (Z = 0.78, p = 0.44), weight (Z = 0.50, p = 0.62), and skinfold thicknesses (Z = 0.45, p = 0.65). Conclusions: The engagement in physical activity during pregnancy exhibits a favorable trend in parameters associated with childhood overweight and obesity while presenting no adverse effects on such outcomes.